(untitled) (Eurasian Research Bulletin, 2023)
The article presents the results of a study of the production of special clothing for car repairmen, taking into account the ergonomic features of a person. Regardless of what type of activity a person is engaged in and how dangerous production is, the worker is affected to one degree or another by many adverse external factors: meteorological, mechanical, chemical, and physical, biological. Therefore, special-purpose clothing plays a paramount role in protecting the health and life of workers. Recently, many small and large companies have emerged offering services for the manufacture of various kinds of special-purpose clothing. However, such products do not always meet accepted safety and quality standards.